Development of solid waste management plan in Kuala Nerus, Terengganu - Nuradibah Hazirah, Mohd Zaki (2016)
Solid Waste disposal and wrong management is both an urban and rural problem. Every person is a potential generator of waste and thus a contributor to this problem. The generation of waste is one thing and the amount of waste generation is another thing. The management and disposal of waste depends on the type of waste generation and it is quite a different issue. Before this, Kuala Nerus was in the district of Kuala Terengganu but after the rapid growth of population and the highest urbanization in that area, Kuala Nerus is declared as a new district in Terengganu. This means that Kuala Nerus will have its own management centre and does not need to rely on management of Kuala Terengganu anymore. This study was carried out in Kuala Nerus Town which is the new district in the state of Terengganu, Malaysia. The main objective of this study was to estimate the type and amount of solid waste generation in Kuala Nerus, Terengganu. The other objective was to make recommendation or suggestion for future action to establish environmentally sound management of solid waste. This study used a combination of both quantitative and qualitative methodologies to research. So, I chose to use document review, observation and interview as the data collection method. The findings revealed that there are a few types of solid waste generated among the community in that area. There are four types of solid waste generated in this area which are paper, plastics, glass and metal. The result obtain shows that the amount of paper generated is 12kg/day while the amount of plastics generated is 10kg/day. Beside that, the amount of metal generated is 13kg/day while the amount of glass generated is 15kg/day. It is also identified that the amount of solid waste generated among the community increases from year to year. From the research, it show that most of the community practice “pit-burning” and also illegal dumping as their method of solid waste disposal. It is observed that people dumped waste along the paths, by the roadsides, in incomplete building structure, in bushes and in bare plots of land without any structures. This study revealed that the majority proportion of public in Kuala Nerus exhibited concern on amount of solid waste generation but sorting of solid waste is less adopted. Therefore, because of the increasing amount of solid waste generated and the low level of public participation in solid waste management in Kuala Nerus, some recommendations have been suggested. The best way to start dealing with the problem is for the Town Council authorities to show the people that they are worth by involving them in the initial planning process.